Ageing Care Centers: Mediating Role of Quality Care and Proactive Environment - Noor, Shaista; Isa, Filzah Md.; Hossain, Md. Sazzad; Shafiq, Ali (Journal of Population and Social Studies [JPSS], 2020)
The aging population has become a significant concern in many countries, including Malaysia. As a developing country, Malaysia is still struggling to provide better care for the elderly segment, which is increasing in number and demands distinctive attention, care, and treatment from both family and society. This study aims to examine the relationship between Perception of Health and Happiness, Behavioral Attitude, Health Promotion, and Education, Quality Care, Proactive Environment, and Elderly Care Services in Aging care centers in Malaysia. A probability simple random sampling technique was utilized in distributing a survey-based questionnaire, and 328 responses were collected from entrepreneurs of both registered and non-registered aging care centers. The research model was assessed using Partial Least Square-Structural Equation Modelling. The remarkable results of the research are: (1) Perception of Health and Happiness do not affect Quality Care and Proactive Environment. (2) Behavioral Attitude, Health Promotion, and Education significantly affect the quality care and Proactive Environment. (3) Quality Care and Proactive Environment significantly mediate the relationship between Behavioral Attitudes, Health Promotion, and Education. (4) Quality Care insignificantly mediates the relationship between Proactive Environment and Perception of Health and Happiness. The findings revealed that Behavioral Attitude, Health Promotion, and Education have a significant effect. Hence, the present study should further be strengthened to enhance the aging care of elderly care center services for the betterment of elderly care centers, especially those that are operated by entrepreneurs. The implication of the study is discussed in the paper.